1996
DOI: 10.1002/(sici)1097-010x(19960101)274:1<1::aid-jez1>3.3.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Physiological adaptations of rainbow trout to chronically elevated water pH (pH = 9.5)

Abstract: Recent investigations have demonstrated that rainbow trout cope with acute high pH (pH > 9.0) exposure (lasting 3–8 days) through their ability to counteract high‐pH‐induced disturbances to ammonia excretion (JAmm), acid‐base homeostasis, and electrolyte balance. In the present investigation our goal was to establish how these physiological processes were modulated during chronic (28‐day) high pH (pH = 9.5) exposure. Chronic high pH led to minimal mortality, and there were no long‐term changes in stress indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 1 publication
3
15
0
Order By: Relevance
“…The present data shows a significant decrease in plasma chloride at 24 h. The subsequent removal of HCO 3 − via the Cl − / HCO 3 − exchanger at the gills may account for the recovery of chloride by 72 h. This is speculative, as we did not measure plasma HCO 3 − ; however soft water high pH studies have shown increases in HCO 3 − as a result of high pH exposure (Heming and Blumhagen, 1988;Yesaki and Iwama, 1992;McGeer and Eddy, 1998). We expected sodium levels to drop as reported in other trout studies (Wilkie et al, 1993(Wilkie et al, , 1996Wilkie and Wood, 1995), but there were no obvious decreases in plasma sodium much like the study by Wilkie et al (1999). The addition of a total of 0.01 M sodium from NaOH may have assisted in maintaining plasma sodium values.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The present data shows a significant decrease in plasma chloride at 24 h. The subsequent removal of HCO 3 − via the Cl − / HCO 3 − exchanger at the gills may account for the recovery of chloride by 72 h. This is speculative, as we did not measure plasma HCO 3 − ; however soft water high pH studies have shown increases in HCO 3 − as a result of high pH exposure (Heming and Blumhagen, 1988;Yesaki and Iwama, 1992;McGeer and Eddy, 1998). We expected sodium levels to drop as reported in other trout studies (Wilkie et al, 1993(Wilkie et al, , 1996Wilkie and Wood, 1995), but there were no obvious decreases in plasma sodium much like the study by Wilkie et al (1999). The addition of a total of 0.01 M sodium from NaOH may have assisted in maintaining plasma sodium values.…”
Section: Discussionsupporting
confidence: 91%
“…Disturbances in ionoregulation occur primarily because high pH causes gill damage by hypertrophy of mucous secreting cells and the degradation of connective tissue between epithelial cells (Daye and Garside, 1976). High pH studies have demonstrated an increase in ion efflux across the gill in freshwater (Wilkie and Wood, 1994;Wilkie et al, 1996), which when coupled with a direct inhibition of ion influx (Wilkie et al, 1999), results in a loss of ions from the plasma.…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…In an enclosure experiment, perch survived at pH 10.0 but died when water pH reach a value of 11.0 (Beklioglu and Moss, 1995), suggesting that pH values in Varese lake were often near the upper limit for perch survival. Several laboratory studies have shown that rainbow trout can survive in high pH water for a considerable period of time (15 days at pH 10.0 and 28 days at pH 9.5), due to adjustments to branchial ion movements, acid-base balance, ammonia excretion and production (Wilkie et al, 1996), which may be similar to mechanisms employed by perch in Slapton Lay and Varese lake. In consideration of the trophic state of lake waters, the cage was positioned in the first three meters of water column from the surface, in order to avoid any problem due to anoxic phenomena in the hypolimnion.…”
Section: Discussionmentioning
confidence: 99%